A "trigger", a cause or obscured? How trauma and adversity are constructed in psychiatric stress-vulnerability accounts of "psychosis". (February 2021) - Harper, David J; O'Donnell, Edward; Platts, Simon
How do mental health professionals link adverse life experiences with the kinds of beliefs and experiences which attract a diagnosis of psychosis and what implications does this have for women with these diagnoses? Drawing on a broadly critical realist framework, we present data from two studies relevant to these questions. First, we analyse the discursive practices engaged in during a staff-only discussion of a female in-patient with a psychosis diagnosis who had been raped some years previously. Staff oriented to the irrationality and factuality of her ostensibly delusional statements about rape and pregnancy in the present and formulated adverse experience as a "stress factor" triggering a manic episode, thereby precluding alternative contextualising interpretations. In a second, interview-based, study, psychiatrists drew on a range of discursive resources which differentiated "psychosis" from other forms of distress, constructed trauma as a stressor which could trigger psychosis because of a genetic predisposition, and constructed medication as the primary intervention whilst trauma was de-emphasised. We discuss the implications of these findings for the kinds of explanations and forms of help offered and suggest ways in which distress might be contextualised as well as possible future directions for feminist research and practice.